Respuestas

  • Usuario de Brainly
2012-09-05T01:12:57+02:00

(2x3 + 5x − 3) + (2x3 − 3x2 + 4x)

 2x3 + 2x3 − 3 x2 + 5x + 4x − 3

4x3 − 3x2 + 9x − 3

7x4 + 6x3 + 4x2 + 15x + 5


resta


(2x3 + 5x − 3) − (2x3 − 3x2 + 4x)

 2x3 + 5x − 3 − 2x3 + 3x2 − 4x

 2x3 − 2x3 + 3x2 + 5x − 4x − 3


¡La mejor respuesta!
2012-09-05T01:13:44+02:00


Suma:

P(x) = 2x3 + 5x − 3    


P(x) +  Q(x) = (2x3 + 5x − 3) + (2x3 − 3x2 + 4x)


 Q(x) = 2x3 − 3x2 + 4x


 Q(x) = 4x − 3x2 + 2x3


Resta:

P(x) − Q(x) = (2x3 + 5x − 3) − (2x3 − 3x2 + 4x)

P(x) −  Q(x) = 2x3 + 5x − 3 − 2x3 + 3x2 − 4x

P(x) −  Q(x) = 2x3 − 2x3 + 3x2 + 5x − 4x − 3

P(x) −  Q(x) = 3x2 + x − 3